Controllability of dynamic systems the Green's function approach - Avetisyan, Ara S. (Cambridge Scholars Publishing, 2018)
"The book is about the possibilities of involvement of the well-known Green's function method in exact or approximate controllability analysis for dynamic systems. Due to existing extensions of the Green's function notion to nonlinear systems, the approach developed here is valid for systems with both linear and nonlinear dynamics. The book offers a number of particular examples, covering specific issues that make the controllability analysis sophisticated, such as coordinate dependent characteristics, point sources, unbounded domains, higher dimensions, and specific nonlinearities. It also offers extensive numerical analysis, which reveals both advantages and drawbacks of the approach. As such, the book will be of interest to researchers interested in the theory and practice of control, as well as PhD and Master's students."--